A imagem do lugar e seus reflexos:um estudo do bairro da Levada. - Nascimento, Bárbara Thomaz Lins do (2008)
The city s inhabitant is able to find in the quarter, different ways to know the urban environment as individual. The quarter shows through simple actions the familiar practices of living as collective neighborhood s relationships. However these actions also reveal different perspectives to valorize the places. Considering this presupposition this research explore the quarter, as an important way to understand the relationship between the man and his urban environment. At this sense, the research uses an image s mental analyses of the place. Through its construction is also explore the importance for understand the fundamental elements for evaluative environments. In order to illustrate this propose, the present research brings results based in the Levada´s district, Maceió, Alagoas. This district passed for the last forty years through transformations that caused the decadence of the area. Although the changes, its presents, until today, an active dynamic that emphasizes to neighborhood as the city. At the same way, shows its importance as an empirical study of the space s elements of the relationship between the man and his urban environment.